A general view of the criminal law of England / James Fitzjames Stephen. - Stephen, James Fitzjames, 1829-1894 (Cambridge library collection., 2014)
The jurist Sir James Fitzjames Stephen (1829-94) published this work in 1863 to provide the intelligent layman with a general account of the workings and principles of English criminal law. He begins with a brief sketch of the development of that law from the Anglo-Saxon period onwards. He then covers the current law on criminal responsibility and the classification and definition of specific crimes, before turning to procedure and the rules of evidence. The book helped to establish Stephen's reputation and made possible his appointment as legal member of the Indian viceroy's council in succession to Henry Maine in 1869. Work on its revision for a second edition led Stephen into producing separate and authoritative digests of the law of evidence, criminal law, and criminal procedure, as well as his three-volume History of the Criminal Law of England, published in 1883 and also reissued in this series.